Brainwave Year - 2014 Science is Just A Game (Amar Chitra Katha Private limited., 2014)
Brainwave Science Magazine simplifies text book science for 8-15 year olds. It makes lessons interesting by presenting them in the form of comics, stories, DIYs, fascinating facts, contests and much more. c